2017
DOI: 10.1128/jvi.00050-17
|View full text |Cite|
|
Sign up to set email alerts
|

Herpes Simplex Virus gE/gI and US9 Promote both Envelopment and Sorting of Virus Particles in the Cytoplasm of Neurons, Two Processes That Precede Anterograde Transport in Axons

Abstract: Herpes simplex virus (HSV) anterograde transport in neuronal axons is vital, allowing spread from latently infected ganglia to epithelial tissues, where viral progeny are produced in numbers allowing spread to other hosts. The HSV membrane proteins gE/gI and US9 initiate the process of anterograde axonal transport, ensuring that virus particles are transported from the cytoplasm into the most proximal segments of axons. These proteins do not appear to be important once HSV is inside axons. We previously descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 46 publications
8
66
0
Order By: Relevance
“…Deletion of the US9 gene clearly results in fewer PRV particles present in axons, nevertheless the kinetics of anterograde transport of those few axonal US9p-null PRV particles were indistinguishable from wild type [194]. Similar data were reported for HSV-1, where simultaneous loss of US9p and gE/gI led to severely diminished numbers of trafficking axonal particles, but those in the axon exhibited normal rates of anterograde traffic [161,189]. One possible explanation is that the reduced numbers of axonal viral particles seen in ∆US9 PRV and ∆US9/∆gE/∆gI HSV-1 strains is due to aberrant trafficking of viral particles within the neuronal cell body, or a failure to efficiently sort virions from the cell body into the axon itself [194].…”
Section: Molecular Roles For Ge/gi and Us9p In Anterograde Transport supporting
confidence: 66%
See 4 more Smart Citations
“…Deletion of the US9 gene clearly results in fewer PRV particles present in axons, nevertheless the kinetics of anterograde transport of those few axonal US9p-null PRV particles were indistinguishable from wild type [194]. Similar data were reported for HSV-1, where simultaneous loss of US9p and gE/gI led to severely diminished numbers of trafficking axonal particles, but those in the axon exhibited normal rates of anterograde traffic [161,189]. One possible explanation is that the reduced numbers of axonal viral particles seen in ∆US9 PRV and ∆US9/∆gE/∆gI HSV-1 strains is due to aberrant trafficking of viral particles within the neuronal cell body, or a failure to efficiently sort virions from the cell body into the axon itself [194].…”
Section: Molecular Roles For Ge/gi and Us9p In Anterograde Transport supporting
confidence: 66%
“…In rat SCGs, one study found only completely assembled enveloped virions (OEVs) within axons upon infection with HSV-1, HSV-2, or PRV [150], but another found a mixture of OEVs and naked capsids in a 3:1 ratio [160]. To reconcile such findings it has been suggested that HSV-1 may have the capacity to utilize both the separate and married transport mechanisms, with varying ratio of naked axonal capsids and OEVs, depending upon the origin of the neurons being studied and how transport is assayed [160][161][162] (see also Section 7.4).…”
Section: Anterograde Trafficking Down the Axon: A Multitude Of Traffimentioning
confidence: 99%
See 3 more Smart Citations